2016
DOI: 10.1080/02680513.2016.1150160
|View full text |Cite
|
Sign up to set email alerts
|

Syrians’ acceptance of digital lectures: a case study

Abstract: The Internet is changing the concept of distance education and universities through its increased involvement in education (Burnett, 2001). Distance education and online instruction have dramatically increased over the last 20 years due to technological advances in the Internet and the prevalence of sophisticated course management systems (Beqiri, Chase, & Bishka, 2010; Wang, 2007). Communication technologies, including the Internet, are facilitating learning through, providing higher education institutions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…It reduces the trouble of distance travel for learning and education [32], [35], empower students to the knowledge of global issues and trends, increasing access to tertiary educations for students who are denied due to reasons such as health, financial, cultural, etc. [7], [36], improve innovativeness [3], and global cultural immersion of students and instructors [2]. Such learning environments make it easier for instructors draw inspirations and examples from around the world.…”
Section: Future Career Opportunities For Instructors and Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…It reduces the trouble of distance travel for learning and education [32], [35], empower students to the knowledge of global issues and trends, increasing access to tertiary educations for students who are denied due to reasons such as health, financial, cultural, etc. [7], [36], improve innovativeness [3], and global cultural immersion of students and instructors [2]. Such learning environments make it easier for instructors draw inspirations and examples from around the world.…”
Section: Future Career Opportunities For Instructors and Studentsmentioning
confidence: 99%
“…Our results show numerous opportunities for e-learning innovation across educational institutions (Universities, Colleges, and Schools) globally. It was observed that e-learning accelerates the quality of education [7], stimulates learning experience [4], [11], lessons the situational and cost barriers to access education [2], [3], and encouraging interaction and immediate feedback between students, and their instructors [6]. Despite the numerous benefits, our content review highlights some of the salient challenges confronting e-learning adoption and diffusion in educational institutions.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For free learning world, Bell and Ramadan showed that Syrians had used challenging strategies which could really shake up the Ivory Tower and offers minds in all places globally the hope of quality education irrespective of income, culture or gender and further had verified Syrians acceptance of digital lectures after 5 years of their country crises [42,43]. Syrian open learning is concerned with two of great issues of our time: Firstly, sustainability, including the qualities and availability of higher education in a global setting -this setting being globalizationthe importance of which was made manifestly clear in the recent cut and thrust evident at the 21 st conference of the Parties to the United Nations Framework Convention on Climate Change (COP21) deliberations in Paris in December 2015.…”
Section: Introductionmentioning
confidence: 99%